Discourse Analysis of The Phenomenon of Career Women in The Context of Family Resilience Through a Socio-Juridical Perspective - Basri, Marlina; Abdul Pirol; Takdir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the phenomenon of career women in the context of family resilience through a socio-juridical perspective. The purpose of this study is to analyses the relationship between the dual roles of career women and family stability and welfare, and to identify the accompanying legal and social implications. Using the critical discourse analysis method, this study explores various aspects that influence the dynamics of career women's lives in maintaining a balance between professional and domestic responsibilities.  The results of the study indicate that the role of career women has a significant impact on family resilience, both in terms of economics, social, and psychology. Economically, career women's financial contributions strengthen the family's economic resilience. However, challenges arise in terms of time division, childcare, and fulfilment of other family functions. This study also reveals the importance of legal and policy support that facilitates the balance of career women's roles, including regulations on women's workers' rights and family protection.  The conclusion of the study emphasizes the need for a holistic approach in understanding and supporting the role of career women in family resilience, by considering the intertwined social, legal, and cultural aspects. Recommendations proposed include strengthening policies that support work-family balance, improving social support systems, and developing empowerment programs that pay attention to the specific needs of career women in the context of family life.